Anti-CD19 CAR T cell therapy for refractory systemic lupus erythematosus - Mackensen, Andreas; Müller, Fabian; Mougiakakos, Dimitrios; Böltz, Sebastian; Wilhelm, Artur; Aigner, Michael; Völkl, Simon; Simon, David; Kleyer, Arnd; Munoz, Luis Enrique; Kretschmann, Sascha; Kharboutli, Soraya; et al. (Nature Medicine, 2022)
Systemic lupus erythematosus (SLE) is a life-threatening autoimmune disease characterized by adaptive immune system activation, formation of double-stranded DNA autoantibodies and organ inflammation. Five patients with SLE (four women and one man) with a median (range) age of 22 (6) years, median (range) disease duration of 4 (8) years and active disease (median (range) SLE disease activity index Systemic Lupus Erythematosus Disease Activity Index: 16 (8)) refractory to several immunosuppressive drug treatments were enrolled in a compassionate-use chimeric antigen receptor (CAR) T cell program. Autologous T cells from patients with SLE were transduced with a lentiviral anti-CD19 CAR vector, expanded and reinfused at a dose of 1 × 106 CAR T cells per kg body weight into the patients after lymphodepletion with fludarabine and cyclophosphamide. CAR T cells expanded in vivo, led to deep depletion of B cells, improvement of clinical symptoms and normalization of laboratory parameters including seroconversion of anti-double-stranded DNA antibodies. Remission of SLE according to DORIS criteria was achieved in all five patients after 3 months and the median (range) Systemic Lupus Erythematosus Disease Activity Index score after 3 months was 0 (2). Drug-free remission was maintained during longer follow-up (median (range) of 8 (12) months after CAR T cell administration) and even after the reappearance of B cells, which was observed after a mean (±s.d.) of 110 ± 32 d after CAR T cell treatment. Reappearing B cells were naïve and showed non-class-switched B cell receptors. CAR T cell treatment was well tolerated with only mild cytokine-release syndrome. These data suggest that CD19 CAR T cell transfer is feasible, tolerable and highly effective in SLE.
CRIS-Team Scopus Importer:2022-09-30

Author Correction: Anti-CD19 CAR T cell therapy for refractory systemic lupus erythematosus. - Mackensen, Andreas; Müller, Fabian; Mougiakakos, Dimitrios; Böltz, Sebastian; Wilhelm, Artur; Aigner, Michael; Völkl, Simon; Simon, David; Kleyer, Arnd; Munoz, Luis Enrique; Kretschmann, Sascha; Kharboutli, Soraya; et al. (Nature Medicine, 2023)
EVALuna2:512812

Bispecific T cell engager therapy for refractory rheumatoid arthritis - Bucci, Laura; Hagen, Melanie; Rothe, Tobias; Raimondo, Maria Gabriella; Fagni, Filippo; Tur, Carlo; Wirsching, Andreas; Wacker, Jochen; Wilhelm, Artur; Auger, Jean-Philippe; Pachowsky, Milena; Eckstein, Markus; et al. (Nature Medicine, 2024)
Bispecific T cell engagers (BiTEs) kill B cells by engaging T cells. BiTEs are highly effective in acute lymphoblastic leukemia. Here we treated six patients with multidrug-resistant rheumatoid arthritis (RA) with the CD19xCD3 BiTE blinatumomab under compassionate use. Low doses of blinatumomab led to B cell depletion and concomitant decrease of T cells, documenting their engager function. Treatment was safe, with brief increase in body temperature and acute phase proteins during first infusion but no signs of clinically relevant cytokine-release syndrome. Blinatumomab led to a rapid decline in RA clinical disease activity in all patients, improved synovitis in ultrasound and FAPI-PET-CT and reduced autoantibodies. High-dimensional flow cytometry analysis of B cells documented an immune reset with depletion of activated memory B cells, which were replaced by nonclass-switched IgD-positive naïve B cells. Together, these data suggest the feasibility and potential for BiTEs to treat RA. This approach warrants further exploration on other B-cell-mediated autoimmune diseases.
CRIS-Team Scopus Importer:2024-05-03

CD19 CAR T-Cell Therapy in Autoimmune Disease - A Case Series with Follow-up. - Müller, Fabian; Taubmann, Jule; Bucci, Laura; Wilhelm, Artur; Bergmann, Christina; Völkl, Simon; Aigner, Michael; Rothe, Tobias; Minopoulou, Ioanna; Tur, Carlo; Knitza, Johannes; Kharboutli, Soraya; et al. (New England Journal of Medicine, 2024)
BACKGROUND: Treatment for autoimmune diseases such as systemic lupus erythematosus (SLE), idiopathic inflammatory myositis, and systemic sclerosis often involves long-term immune suppression. Resetting aberrant autoimmunity in these diseases through deep depletion of B cells is a potential strategy for achieving sustained drug-free remission. METHODS: We evaluated 15 patients with severe SLE (8 patients), idiopathic inflammatory myositis (3 patients), or systemic sclerosis (4 patients) who received a single infusion of CD19 chimeric antigen receptor (CAR) T cells after preconditioning with fludarabine and cyclophosphamide. Efficacy up to 2 years after CAR T-cell infusion was assessed by means of Definition of Remission in SLE (DORIS) remission criteria, American College of Rheumatology-European League against Rheumatism (ACR-EULAR) major clinical response, and the score on the European Scleroderma Trials and Research Group (EUSTAR) activity index (with higher scores indicating greater disease activity), among others. Safety variables, including cytokine release syndrome and infections, were recorded. RESULTS: The median follow-up was 15 months (range, 4 to 29). The mean (±SD) duration of B-cell aplasia was 112±47 days. All the patients with SLE had DORIS remission, all the patients with idiopathic inflammatory myositis had an ACR-EULAR major clinical response, and all the patients with systemic sclerosis had a decrease in the score on the EUSTAR activity index. Immunosuppressive therapy was completely stopped in all the patients. Grade 1 cytokine release syndrome occurred in 10 patients. One patient each had grade 2 cytokine release syndrome, grade 1 immune effector cell-associated neurotoxicity syndrome, and pneumonia that resulted in hospitalization. CONCLUSIONS: In this case series, CD19 CAR T-cell transfer appeared to be feasible, safe, and efficacious in three different autoimmune diseases, providing rationale for further controlled clinical trials. (Funded by Deutsche Forschungsgemeinschaft and others.).
EVALuna2:555903

Metabolic profiling of single cells by exploiting NADH and FAD fluorescence via flow cytometry - Abir, Ariful Haque; Weckwerth, Leonie; Wilhelm, Artur; Thomas, Jana; Reichardt, Clara; Munoz, Luis Enrique; Völkl, Simon; Appelt, Uwe; Mroz, Markus; Niesner, Raluca; Hauser, Anja; Fischer, Rebecca Sophie; et al. (Molecular Metabolism, 2024)
Objective: The metabolism of different cells within the same microenvironment can differ and dictate physiological or pathological adaptions. Current single-cell analysis methods of metabolism are not label-free. Methods: The study introduces a label-free, live-cell analysis method assessing endogenous fluorescence of NAD(P)H and FAD in surface-stained cells by flow cytometry. Results: OxPhos inhibition, mitochondrial uncoupling, glucose exposure, genetic inactivation of glucose uptake and mitochondrial respiration alter the optical redox ratios of FAD and NAD(P)H as measured by flow cytometry. Those alterations correlate strongly with measurements obtained by extracellular flux analysis. Consequently, metabolically distinct live B-cell populations can be resolved, showing that human memory B-cells from peripheral blood exhibit a higher glycolytic flexibility than naïve B cells. Moreover, the comparison of blood-derived B- and T-lymphocytes from healthy donors and rheumatoid arthritis patients unleashes rheumatoid arthritis-associated metabolic traits in human naïve and memory B-lymphocytes. Conclusions: Taken together, these data show that the optical redox ratio can depict metabolic differences in distinct cell populations by flow cytometry.
CRIS-Team Scopus Importer:2024-07-19
Keywords: FAD; Flow cytometry; Fluorescence; Metabolism; NADH; Real-time

Selective CAR T cell–mediated B cell depletion suppresses IFN signature in SLE - Wilhelm, Artur; Chambers, David; Müller, Fabian; Bozec, Aline; Grieshaber Bouyer, Ricardo; Winkler, Thomas; Mougiakakos, Dimitrios; Mackensen, Andreas; Schett, Georg; Krönke, Gerhard (JCI Insight, 2024)
Applying advanced molecular profiling together with highly specific targeted therapies offers the possibility to better dissect the mechanisms underlying immune-mediated inflammatory diseases such as systemic lupus erythematosus (SLE) in humans. Here we apply a combination of single-cell RNA-Seq and T/B cell repertoire analysis to perform an in-depth characterization of molecular changes in the immune-signature upon CD19 CAR T cell–mediated depletion of B cells in patients with SLE. The resulting data sets not only confirm a selective CAR T cell–mediated reset of the B cell response but simultaneously reveal consequent changes in the transcriptional signature of monocyte and T cell subsets that respond with a profound reduction in type I IFN signaling. Our current data, thus, provide evidence for a causal relationship between the B cell response and the increased IFN signature observed in SLE and additionally demonstrate the usefulness of combining targeted therapies and analytic approaches to decipher molecular mechanisms of immune-mediated inflammatory diseases in humans.
CRIS-Team Scopus Importer:2024-07-12